Comparing the microstructure and mechanical properties of Bombyx mori and Antheraea pernyi cocoon composites. (1st January 2017) - Guan, Juan; Zhu, Wenshu; Liu, Binghe; Yang, Kang; Vollrath, Fritz; Xu, Jun
Graphical abstract: Abstract: Silkworm cocoon material is a natural composite consisting of silk fibres and sericin glues. Both domestic and wild silkworms produce cocoons but with different functionality – one selected by man for textile manufacture whereas the other selected by Nature to provide damage-tolerant housing. To understand the structure-–property relationship of cocoons, we evaluated and compared the microstructure and mechanical properties of two representative cocoon walls. It appears that a "brittle and weak" composite is produced by domestic Bombyx mori ( B. mori ) while a "tough and strong" composite is made by wild Antheraea pernyi ( A. pernyi ). The superior mechanical performance of A. pernyi cocoons can be attributed to both the material properties and the fibre network microstructures. Failure mechanisms and different failure modes for cocoon fibre composites were also proposed. A finite element model revealed qualitatively the effect of fibre properties and inter-fibre bonding strength on the mechanical properties of the fibre network. It emerged that both good mechanical properties of fibres and robust inter-fibre bonding were required for tough and strong fibre composites. The new insights could inspire new designs of synthetic fibre composites with enhanced mechanical properties. Statement of Significance: Natural cocoons are an important group of natural fibre composites with versatile functionalities. Previous studies have focused on the diversity of cocoon species and different morphological and mechanical features. It was suggested that the cocoon network structure determined the final mechanical properties of the cocoon composite. Nevertheless, the full structure–propertyfunction relationships for the cocoon composite are not understood. By studying two distinct cocoon species with specific functionalities, we prove that the mechanical properties of two cocoons are determined by both network properties and fibre properties. A robust fibre network is the prerequisite, within which the good mechanical properties of the fibres can play a part. The finding will inspire new designs of synthetic composites with desirable and predictable mechanical properties.